Icelandic translation, adaptation and validation of the Parental Burnout Assessment (PBA-IS) - Helga Sif Pétursdóttir; Eva Halapi; Björg Thordardottir (Scandinavian Journal of Occupational Therapy)
Background As parental burnout is increasingly recognised for its severe impact on parents and children, identifying factors that exacerbate or alleviate this condition is crucial. Reliable assessment tools in clinical settings are essential to detect those at risk of or experiencing burnout, enabling timely intervention.Aims/objectives This study aims to adapt the Parental Burnout Assessment for use in Iceland and evaluate its psychometric properties while exploring how personal and socio-demographic factors influence parental burnout.Materials and methods A sample of 1,110 parents participated. Descriptive statistics analysed the main dataset characteristics, and confirmatory factor analysis evaluated the psychometric properties of the adapted version.Results Satisfactory structural validity and internal consistency (α 0.96) of the PBA-IS was demonstrated. Factors influencing parental burnout included marital status, number of children, perceived support, and personal causation.Conclusions The PBA-IS is a valid and reliable translated tool for assessing parental burnout in Iceland. Personal causation, a key concept in occupational therapy, appears pivotal in parental burnout. Occupational therapists can provide holistic support to help parents effectively manage stress.Significance The PBA-IS enables parental burnout to be identified in Icelandic clinical settings, supporting early interventions that reduce stress, promote mental health, and enhance well-being.